Intensity noise reduction using a gain saturated soa [electronic resource) - Kanar Roshen Tariq 1987-; David, Ian Fosyth (2014)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2014